Activation of the human "beta 2-interferon/hepatocyte-stimulating factor/interleukin 6" promoter by cytokines, viruses, and second messenger agonists. - Ray, A (1988)
The hallmark of "beta 2-interferon (IFN-beta 2)/hepatocyte-stimulating factor/interleukin 6" gene expression is its inducibility in different types of human cells (fibroblasts, monocytes, epithelial cells, and endothelial cells) by different stimuli, which include cytokines such as tumor necrosis factor, interleukin 1 (IL-1) and platelet-derived growth factor, different viruses, and bacterial products such as endotoxin. The activation by cytokines, viruses, and second messenger agonists of the IFN-beta 2 promoter linked to the bacterial chloramphenicol acetyltransferase (CAT) gene was studied after transfection into HeLa cells. A chimeric gene containing IFN-beta 2 DNA from -1180 to +13 linked to the CAT gene was inducible approximately 10-fold by phorbol 12-myristate 13-acetate (PMA), followed, in decreasing order, by pseudorabies and Sendai viruses (7- to 11-fold each); serum (6- to 9-fold); the cytokines tumor necrosis factor, IL-1, and epidermal growth factor (3- to 5-fold each); the cAMP agonists BrcAMP and forskolin and the phosphodiesterase inhibitor 3-isobutyl-1-methylxanthine (2- to 6-fold each); poly(I).poly(C) (2- to 4-fold); 1,2-diacylglycerol and the calcium ionophore A23187 (1.5- to 2-fold each). Bacterial endotoxin did not activate this IFN-beta 2/CAT fusion gene in HeLa cells. Deletion of the 5' boundary of the IFN-beta 2 DNA from -1180 to -596 in the fusion gene preserved its activation by IL-1, tumor necrosis factor, epidermal growth factor, serum, pseudorabies, and Sendai viruses and by PMA, Br-cAMP, and forskolin; deletion to -225 led to a small reduction (by a factor of 1.5-2) in the responsiveness to serum, PMA, and Sendai virus but not to the other inducers; a further deletion to -112 greatly reduced all responsiveness. Thus, the region between -225 and -113 in IFN-beta 2, which contains DNA motifs similar to the regulatory elements in the human c-fos gene, appears to contain the major cis-acting regulatory elements responsible for the activation of the IFN-beta 2 promoter by several different cytokines, viruses, and second messenger agonists.